The determination of digestibility of ammonia treated wheat straw and its effect on growth performance of beef cattle - Behiç Coşkun; Suphi Deniz; Ali Ayar; Ramazan Kadak; Fazıl Deligözoğlu (Eurasian Journal of Veterinary Sciences)
This experiment was conducted to investigate the effects of treatment of wheat straw with aqueous ammonia on its digestibility and feed intake and weight gain of beef cattle fed two level of concentrate mixture. About five tones wheat straw stack treated with 40 g aqueous ammonia contains 25 % NH3 per kg straw for 30 days after covering the stack with plastic sheet. The digestibilities of untreated and treated straw was determined with four Merino rams. The digestibilities of dry mat. ter, crude protein, crude fibre, organic matter were 47.74, 58.80, 58.83 and 49.22 % for untreated straw and 49.59, 73.42,63.35,52.92 % for treated straw, respectively. In the feeding experiment, 28 bulls were allocated to four groups each of 7 bulls. Two level of concentrate mixture and two straw (treated and untreated) were given with a 2x2 factorial arrangement. The ammonia treatment decreased straw intake. No differences in the live weights gain were found among the groups.